Rice Doctor Odisha - CGIAR Research Program on Rice (2019)
During Kharif 2018, usability testing of Rice Doctor was done with extension advisors, students and progressive farmers. The entire content of Rice Doctor was translated to Odisha. The changes/corrections suggested during user testing were incorporated to Odisha version of Rice which is ready for dissemination.